Rahnella aquatilis JZ-GX1 alleviates iron deficiency chlorosis in Cinnamomum camphora by secreting desferrioxamine and reshaping the soil fungal community - Kong, Wei-Liang; Wang, Ya-Hui; Lu, Lan-Xiang; Li, Pu-Sheng; Zhang, Yu; Wu, Xiao-Qin (Frontiers in Plant Science, 2022)
Plant growth-promoting rhizobacteria are important for improving plant iron nutrition, but the interactions among inoculants, host plants and soil microorganisms have not been greatly explored. Rahnella aquatilis JZ-GX1 was applied to treat the increasingly serious iron deficiency chlorosis in Cinnamomum camphora, and the resulting improvement in chlorosis was determined by assessing the contents of chlorophyll, active iron, Fe2+ and antioxidant enzymes in leaves, the effects on the soil microbial community and the metabolism in the rhizosphere by high-throughput sequencing techniques and liquid chromatography–mass spectrometry (LC–MS). The results showed that inoculation with JZ-GX1 significantly increased the chlorophyll content of C. camphora, which promoted the redistribution of active iron in roots and leaves, increased the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX), and thus reduced membrane damage in iron-deficient C. camphora caused by reactive oxygen species. According to genome prediction and ultra-performance liquid chromatography–mass spectrometry (UPLC–MS) analysis, the JZ-GX1 strain could secrete desferrioxamine (DFO), and the concentration of DFO in C. camphora rhizosphere was 21-fold higher than that in uninoculated soil. The exogenous application of DFO increased the SPAD and Fe2+ contents in leaves. In addition, the inoculant affected the fungal community structure and composition in the C. camphora rhizosphere soil and increased the abundances of specific taxa, such as Glomus, Mortierella, Trichoderma, and Penicillium. Therefore, R. aquatilis JZ-GX1 application promoted iron absorption in C. camphora trees by secreting DFO and alleviated iron deficiency chlorosis through interactions with the local fungal community.